A Perspective Study of Pogostemon cablin Benth as an Aphrodisiac - Khairan, Khairan; Amanda, Rosi; Hasbi, Salsa Yubila; Diah, Muhammad; Hasballah, Kartini (Heca Sentra Analitika, 2023)
Pogostemon cablin Benth also known as a patchouli plant, is a member of Lamiaceae family, and the source of patchouli essential oil. This plant is an important herb which possesses many therapeutic properties. In traditional medicinal practices, patchouli oil is used to relieve depression, stress, calm nerves, control appetite and to improve sexual interest. Up to the present moment, almost 200 volatile and non-volatile compounds have been isolated and identified from Pogostemon cablin including flavonoid, phytosterols, glycosides, terpenes, sesquiterpenes, organic acids, and others. Modern studies revealed that the patchouli plant have been used for various applications such as an antioxidant, anti-inflammatory, analgesic, antidepressant, antithrombotic, antiplatelet, fibrinolytic, antiemetic, antimutagenic, and aphrodisiac. In aromatherapy, this plant is believed to be able to improve blood circulation and sexual interest. The flavonoid compounds, such as acacetin and apigenin are believed to play an important role as an aphrodisiac. The mechanisms of action of this plant as an aphrodisiac is believed by increasing androgens and estrogen levels in dehydroepiandrosterone (DHEA), which further increases arousal sexual desire. However, some uses need to be verified and may require standardizing and authenticating the bioactivity of purified compounds through scientific methods. This perspective study discusses the aphrodisiac potential of Pogostemon cablin Benth, including their chemical constituents, health benefit, mechanism action, and the role of main bioactive compound as an aphrodisiac.